Urban rail investment and transit-oriented development in Beijing: Can it reach a higher potential?. (July 2016) - Yang, Jiawen; Quan, Jige; Yan, Bin; He, Canfei
Highlights: Impacts of urban rail on land development in Beijing is sizable but not ubiquitous. Lack of transparency in planning weakens the impacts of urban rail investment. Lack of supportive transit-priority policies also weakens the impacts. Competition in land transaction enhances station-orientation. Abstract: As a response to severe urban congestion, megacities in China have sped up investment in urban rail transit. How effective urban rail investment and relevant planning activities can attract development in China's megacities has rarely been studied. Using eight years' land transaction data in Beijing (2004–2011), this research finds that the market environment in general supports higher density development around transit stations. However, relevant land market regulations and planning practices may prevent the development outcome from reaching its market potential. City governments should adjust existing planning and policy efforts, including more transparent and open process for station location selection, a better articulated investment program that improves transit service, social service and infrastructure quality in suburbs, a shift toward transaction modes of more competition, and a development guidance that grants density bonus to projects closer to metro stations.